An Act for Regulating the Militia of the Province of Maryland, in Votes and Proceedings of the Lower House of Assembly of the Province of Maryland (22 May, 1756) - (:unkn) unknown (My University, 1756)
Prohibited the sale of strong liquor within five miles of any place of militia training.
Keywords: ARMED FORCES